ADSMPE - Uma abordagem para desenvolvimento de software em micro e pequenas empresas - Fernandes, Douglas Bueno (2011)
Nowadays, micro and small companies - MPEs has occupied a significant place in the national economy, this is mainly due the generation of employment and income. According to the Brazilian Association of Software - ABES, in 2010, the software industry and services grew 24%, especially by increasing the production of computer programs on demand, in the same year reached 35% of the national market. Despite of the growth of the market, the MPEs have faced great challenges to remain competitive, the lack of financial resources and lack of a specific development process for smaller-sized companies are some of the difficulties. Ahead this context, this paper presents an approach to software development aimed at micro and small companies, focusing the level G of the Brazilian Model for Software Process Improvement - MPS.BR. The approach is consisted by a set of five phases: Phase I - Initial Contact; Phase II - Requirements; Phase III - Development; Phase IV - Testing and Phase V - Project Completion and Delivery. The approach was evaluated by Experimental Software Engineering, including project managers, members of software development companies, developers and quality managers. Based on the evaluation, it was observed that the approach can be considered a useful tool for the development of systems in MPEs, contributing to the process of improving in the companies.